2016
DOI: 10.1055/s-0042-114523
|View full text |Cite
|
Sign up to set email alerts
|

Klinische Klassifikation der pulmonalen Hypertonie und initiale Diagnostik: Empfehlungen der Kölner Konsensus Konferenz 2016

Abstract: The 2015 European Guidelines on Diagnosis and Treatment of Pulmonary Hypertension are also valid for Germany. The guidelines contain detailed information about the clinical classification and diagnosis of pulmonary hypertension, and furthermore provide novel recommendations for risk stratification and follow-up assessments. However, the practical implementation of the European Guidelines in Germany requires the consideration of several country-specific issues and already existing novel data. This requires a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
3
0
3
Order By: Relevance
“…Recent data has shown that the normal PAPm at rest is 14 + 3 mm Hg with an upper limit of normal of approximately 20 mm Hg [2]. In the new joined guidelines of the European societies for respiratory medicine and cardiology for the diagnosis and treatment of PH, transthoracic color-Doppler-echocardiography (TTE) plays a central role in diagnostic work-up [1,3,4]. It should be used to visualize the effects of PH on the heart and to estimate systolic pulmonary artery pressures through continuous wave Doppler measurements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data has shown that the normal PAPm at rest is 14 + 3 mm Hg with an upper limit of normal of approximately 20 mm Hg [2]. In the new joined guidelines of the European societies for respiratory medicine and cardiology for the diagnosis and treatment of PH, transthoracic color-Doppler-echocardiography (TTE) plays a central role in diagnostic work-up [1,3,4]. It should be used to visualize the effects of PH on the heart and to estimate systolic pulmonary artery pressures through continuous wave Doppler measurements.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, TRV is a well-established and most widely used TTE parameter for noninvasive determination of pulmonary pressure [7]. However, the cut-off values proposed in the current ESC/ERS guidelines for establishing the probability of PH are more or less arbitrary and have not yet been scientifically evaluated or validated for PH [3,4,8]. Retrospective data from a large cohort of patients with high pre-test probability suggests that in experienced hands determining the systolic pulmonary artery pressure using the TRV and estimated right atrial pressure (RAP) correlated well with the invasively measured values (r = 0.87) and, when the suggested limit (36 mm Hg) was used, it has a specificity of 79% and a sensitivity of 87% to detect PH [9].…”
Section: Introductionmentioning
confidence: 99%
“…Die Diagnostik sollte primär in spezialisierten Expertenzentren durchgeführt werden. In Anlehnung an die ESC/ ERS-Leitlinien empfehlen die Deutschen Fachgesellschaften (DGK, DGP, DGPK) im Rahmen der "Kölner Konsensus-Konferenz" ein strukturiertes Vorgehen [10,11] (▶ Abb. 2).…”
Section: Klinische Klassifikationunclassified
“…Hierbei ist insbesondere die Unterscheidung zwischen prä-und postkapillärer pulmonaler Hypertonie wichtig. Die Kölner Konsensus-Konferenz weist in diesem Zusammenhang auch auf die Bedeutung der Spiroergometrie sowohl in der Früherkennung als auch in der Differenzialdiagnostik der PH hin, da hiermit unter Belastung bereits frühzeitig Zeichen einer pulmonalen Vaskulopathie zu detektieren sind [10,11]. Für Patienten mit neu aufgetretener Symptomatik und Verdacht auf eine relevante pulmonale Hypertonie sollte für die initiale Diagnosestellung ein "Fast-Track-Referral" angeboten werden [12], um eine zügige Therapieeinleitung gewährleisten zu können.…”
Section: Klinische Klassifikationunclassified
See 1 more Smart Citation